2006
DOI: 10.1111/j.1365-2141.2006.05997.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of vaccination with dendritic‐like leukaemia cells for the immunotherapy of acute myeloid leukaemia

Abstract: Summary Twenty‐two patients with acute myeloid leukaemia were recruited into a phase I/II clinical trial investigating the vaccination of patients in complete remission (CR) with autologous dendritic‐like leukaemia cells (DLLC). At trial entry, leukaemia cells were harvested and tested for their ability to undergo cytokine‐induced dendritic cell differentiation. Patients were then treated with intensive chemotherapy. Five patients achieved both CR and had leukaemia cells that successfully underwent differentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 16 publications
(17 reference statements)
2
69
0
Order By: Relevance
“…In both cases with the mutation, most of fluorescent intensity at codon 617 was V617F and the wild type was only faintly visible, suggesting that most of the leukemic cells expressed V617F. A previous study found a high occurrence of the JAK2 V617F mutation in RA with ringed sideroblasts associated with marked thrombocytosis (71%), 7 and this mutation has also been detected in MDS with myelofibrosis (33%). 8 In our two cases with the mutation, neither thrombocytosis nor myelofibrosis was detected (Table 2).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…In both cases with the mutation, most of fluorescent intensity at codon 617 was V617F and the wild type was only faintly visible, suggesting that most of the leukemic cells expressed V617F. A previous study found a high occurrence of the JAK2 V617F mutation in RA with ringed sideroblasts associated with marked thrombocytosis (71%), 7 and this mutation has also been detected in MDS with myelofibrosis (33%). 8 In our two cases with the mutation, neither thrombocytosis nor myelofibrosis was detected (Table 2).…”
mentioning
confidence: 97%
“…4 Overall results of Phase I/II clinical trials with autologous DC in AML patients were that vaccination with DC is feasible and safe, although not clinically effective in every patient. 7,8 Obstacles of these clinical approaches are that clinically relevant numbers of efficient DC and CTL have to be prepared or a monitoring of the specificity of CTLs is necessary. So far, a quantification of DC was performed by microscopical counting of cells exhibiting DC characteristics (cell shape, dendrites), although differentiation of DC from cells with similar morphology (e.g.…”
mentioning
confidence: 99%
“…So far, only a limited rate of objective tumor regressions has been observed in clinical studies [3,5,9,14,25,27,44]. One reason for the discrepancy between the outcomes as seen in the pre-clinical feasibility assays with respect to the true clinical responses could be that most pre-clinical in vitro tumor models that evaluate direct cytotoxicity of DCs have been performed on either cancer cell lines or mice models [22,30,31,41,52].…”
Section: Discussionmentioning
confidence: 99%
“…Cytotoxic T-cells have been detected as crucial mediators of the graft-versusleukaemia (GVL) reaction after SCT, although relapses occur (Kolb et al 2004). DLIs can be applied therapeutically for treatment of relapse after SCT or prophylactically in order to stabilize remissions -indicating again the central role of T-cells (Roddie et al 2006;Barrett & Savani 2006;Schmid et al 2007). For an improvement of therapy of AML-/MDS-pts at relapse after SCT GM-CSF might be applied in the context of DLI in order to facilitate the generation of APC from leukaemic blasts and thereby to increase antileukaemic activities of donor T-cells against myeloid blasts, as already shown by others and us in ex vivo settings (Kufner et al 2005;Kremser et al 2010;Schmid et al 2011;Dreyßig et al 2011).…”
Section: Role Of T-cells and DC In Immunotherapy Of Aml And Mdsmentioning
confidence: 99%
“…An interesting immunotherapeutic option to treat cancer and leukaemia are dendritic cell (DC) based strategies (Claxton et al 2001;Roddie et al 2006). DCs are antigen presenting cells (APC) that stimulate a variety of cells both of the innate and adaptive immune systems (e.g.…”
Section: Introductionmentioning
confidence: 99%